'Collar propagation' as an alternative propagation method for rhizomatous miscanthus. Issue 3 (21st September 2017) - Mangold, Anja; Lewandowski, Iris; Xue, Shuai; Kiesel, Andreas
Abstract: The demand for perennial nonfood crops, such as miscanthus, is increasing steadily, as fossil resources are replaced by biomass. However, as the establishment of miscanthus is very expensive, its cultivation area in Europe is still small. The most common propagation method for miscanthus is via rhizomes, the harvesting of which is very labour‐intensive. Seed propagation is promising, but not suitable for sterile genotypes. In this study, a new vegetative propagation method, 'collar propagation', was tested in field and controlled environment studies. Collars are built at the junction between rhizome and stem. They can be harvested in a less destructive way than rhizomes by pulling out the stems from winter‐dormant miscanthus plants. One genotype of each of the species M. sacchariflorus, M. × giganteus, M. sinensis in combination with three fragment types (collars, rhizomes, collars + rhizomes) were tested for establishment success and plant performance. The performance (e.g. dry matter yield) of collar‐propagated plants was either better than or not significantly different from rhizome‐propagated plants. Pregrown plantlets transplanted into the field showed no significant differences in establishment success between the fragments within a genotype. When directly planted into the field however, the fragment 'rhizome+collar' had a significantly better establishment success than the other two. The winter survival rate of the fragment 'rhizome+collar' was 70% for M. sacchariflorus and 75% for M. × giganteus . Emergence success from collar‐derived plants was not affected by harvest date (harvested monthly from November to February). This study showed that miscanthus propagation via collars is feasible and a promising alternative to rhizome propagation, as the multiplication rate of collars is comparable to that of rhizome propagation. Collar propagation is the more suitable method for the tested genotypes of the species M. sachariflorus and M. × giganteus, but not for M. sinensis genotypes, which may be better propagated by seeds.